Desafios para o financiamento da proteç\~ao social no brasil: O Fundo de Amparo ao Trabalhador (FAT) e sua dinâmica orçamentária (2010-2022) - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study aimed to analyze the budget trajectory of the Workers' Support Fund (FAT), contrasting accounting indicators with political and economic factors that may have conditioned its operational planning. The data analysis allowed us to corroborate the hypothesis that the evolution of both revenues and current expenses, in addition to being directly related to ongoing transformations in the Brazilian macroeconomic and occupational structure, proved to be subject to factors external to its governance that interfere in the dynamics fund operations. Such factors are mainly associated with fiscal policy decisions that affected the FAT's financing structure, causing significant revenue losses and compromising financial availability to meet its programmatic social protection demands.
Keywords: E62; H53; J38; J68; 330; work; social protection; public budget; social rights; equal opportunities